??? ??????? (1 KGS 3:9): receiving and forming towards a listening heart - N. Cachia (Acta Theologica)
This reflection article studies the request made by King Solomon to God for “a listening heart” (1 Kgs 3:9) at the beginning of his reign. It shows that this request entails a deliberate and conscious openness of the whole person to God as well as an attentiveness to the demands of the people whom he is called to govern. In Christianity, the “contemplative listening” is intimately linked with the theological tradition of the spiritual senses, which are referred to as the human capacity to know God. This capacity ought to be discovered and developed through formation and self-commitment. In the Christian tradition Spiritual Direction is highly esteemed as a most useful tool for the achievement of this ability, which would then help the person to be transformed into Christ.